Gus Baha’s Perspective on Religious Tolerance and How the Public Respond - Khristianto, Khristianto; Pujiyatno, Ambar; Saepudin, Encep; Al Aqad, Mohammed H. (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Tolerance in religion practices among different groups or differen religious communities is always important in plural societies like Indonesia. However, the fact shows that many intolarance cases still occur in the country. This study is an endevour to explore the tolerance teaching brought by Gus Baha in his traditional islamic lectures. In addition, the reaction of the public to the teaching was also examined. It adopted a digital ethnography approach employing virtual data as the main sources, including YouTube Video, and the comments of netizen following them. The ideas of tolerance were analyzed thematically, and the comments were classified, following the Appraisal theory (Martin & Rose, 2005). Based on the analysis, it reveals that Gus Baha makes use of old stories involving prophets, the Prophet and his companion as they implemented tolerant practices of daily business and religious matters. The stories there proved upscaled tolerance exemplified by the best models for Moslem communities. The public (netizen) have shown positive responses toward the ideas, as it is proved from their positive emotion (80%), and judgment (74%), meaning they like the idea and agree that they are right. In turn, it is expected that they would practice the models of tolerance in their own daily lives.